Pioneering Ideas on Fuzzy Logic in al-Miyānajī's Philosophy - Mehmet Emin Koç (Artuklu Akademi)

(untitled)
It is possible to say that human thinking and logic began with his existence. Although Aristotle, who shaped the world of thought of humanity for two thousand years, is regarded as the father of logic, logic and correct thinking existed before and after him. In this process, Islamic philosophers such as al-Fārābī and Ibn Sina made important contributions. Al-Ghazālī, on the other hand, made Aristotle's logic digested by Islamic schools of thought. Over time, there were philosophers who challenged classical logic and introduced different methods of logic that would surpass it. Among these philosophers, one of the pinnacle figures who had a serious influence on the following periods is ‘Ayn al-Qudāt al-Hamadānī al-Miyānajī. al-Miyānajī influenced the following periods both with his views on the philosophy of existence and with his unique logical propositions and principles of thinking that have survived to this day. It can be said that al-Miānajī is the first precursor of the quantum system, the theory of relativity and fuzzy logic. Addressing his views in the context of understanding the background of the era of Informatics and Artificial Intelligence will make a different contribution to our world of philosophy, logic and thought.